Bang Rajan the legend of the village of warriors - Jitnukul, Tanit; Ngamdee, Jaran; Kraibutr, Winai; Pratyabamrung, Theerayug; Wateela, Uncle Adirek; Film Bangkok ([Malaysia] : Speedy Video (distributor), 2005)
Oliver Stone presents the true story of a rural 18th century Siamese village that managed to battle an army of 100,000 invading Burmese soldiers to a standstill for five months. When Bang Rajan's fearless warrior chief (Chumporn Taephitak) is wounded in battle, the men of the village elect a mighty rogue fighter who has been making raids on Burmese supply lines, Chan (Jaran Ngamdee), to step in and guide them. Along with the village's sage Buddhist priest (Teerayuth Pratyabamrung), Chan inspires the villagers to new heights of courage. In between bouts of bloodshed there are some subplots. One concerns the wife (Bongkod Kongmalia) of one of the mightiest fighters, Nai In (Winai Kraibutr). She learns she's pregnant, and fears her husband will lose his fighting spirit if he finds out. In another, a young warrior named Muang (Atthakorn Suwannaraj) fights to impress the chief's warrior daughter (Soontree Maila-or)
Title from title screen
Director of photography, Vichien Ruangvichayuki ; composer, Chatchai Pongprapaphan
Casts : Winnai Kraibutr, Jaran Ngamdee, Bin Banleurit, Teerayuth Pratyabamrung, Chumporn Taephtak, Atthakorn Suwannaraj, Bongkod Kongmalai, Soontree Maila-or
Thailand version with Mandarin and Malay subtitles
Keywords: Muay Thai -- Drama; Martial artists -- Drama; Foreign films -- Thailand; Historical films; Thailand -- History -- To 1782 -- Drama; Phra Nakhon Si Ayutthaya (Thailand) -- Drama